Embedding Research in Clinical Practice: The Integrated Research Enablement Framework ( IREF ) - Tracy Flenady (Australian Journal of Rural Health, 2026)
ABSTRACT Objective Despite sustained investment in research capacity building, embedding research within clinical practice remains challenging, particularly within regional, rural and remote healthcare settings where workforce shortages, geographic dispersion and limited research infrastructure constrain research engagement. This paper presents the Integrated Research Enablement Framework (IREF), explaining how clinician‐led research is activated, supported and embedded within healthcare settings. Methods A theory‐informed framework development approach integrated cumulative empirical evidence generated through 9 years of implementation and evaluation of a regional research capacity building program with an interpretive synthesis of relevant research capacity building and implementation science literature. Framework development iteratively integrated empirical observations and theoretical models to identify mechanisms underpinning research enablement. Results The IREF comprises three interdependent domains: capability development, relational expertise and enabling infrastructure. These operate through integrated mechanisms including facilitation, mentorship, organisational alignment and resourcing, to support the activation, sustainment and embedding of clinician‐led research. The framework conceptualises research capability development as a relational, practice‐integrated process responsive to the contextual realities of regional and rural healthcare delivery. Conclusion The IREF complements existing research capacity building and implementation science frameworks by explicitly articulating the mechanisms through which clinician‐led research becomes embedded within routine clinical practice. It provides an operational framework for developing research capability while strengthening the organisational conditions required to sustain research within healthcare systems.